2001
DOI: 10.1161/01.cir.103.1.113
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy-Methylglutaryl–Coenzyme A Reductase Inhibition Promotes Endothelial Nitric Oxide Synthase Activation Through a Decrease in Caveolin Abundance

Abstract: We provide biochemical and functional evidence that atorvastatin promotes NO production by decreasing caveolin-1 expression in ECs, regardless of the level of extracellular LDL-Chol. These findings highlight the therapeutic potential of inhibiting cholesterol synthesis in peripheral cells to correct NO-dependent endothelial dysfunction associated with hypercholesterolemia and possibly other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
234
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(249 citation statements)
references
References 22 publications
7
234
1
7
Order By: Relevance
“…Western blots revealed no overt change in the expression levels of NO synthases (i.e., eNOS and inducible NOS) in the heart and lung from the cav-1 Ϫ/Ϫ mouse (data not shown), suggesting that the high NO level was most likely caused by an elevation in eNOS activity resulting in massive NO production. This finding is in agreement with recent in vitro studies that hypercholesterolemia decreased NO production by promoting the interaction of Cav-1 and eNOS and a decrease in Cav-1 abundance through atorvastatin, an inhibitor of hydroxymethylglutaryl-CoA reductase, can promote eNOS activation (26,27).…”
Section: Cav-1 Deficiency Causes Pulmonary Hypertension and Resultingsupporting
confidence: 93%
See 1 more Smart Citation
“…Western blots revealed no overt change in the expression levels of NO synthases (i.e., eNOS and inducible NOS) in the heart and lung from the cav-1 Ϫ/Ϫ mouse (data not shown), suggesting that the high NO level was most likely caused by an elevation in eNOS activity resulting in massive NO production. This finding is in agreement with recent in vitro studies that hypercholesterolemia decreased NO production by promoting the interaction of Cav-1 and eNOS and a decrease in Cav-1 abundance through atorvastatin, an inhibitor of hydroxymethylglutaryl-CoA reductase, can promote eNOS activation (26,27).…”
Section: Cav-1 Deficiency Causes Pulmonary Hypertension and Resultingsupporting
confidence: 93%
“…The consequence for eNOS function of this cholesterol-induced increase in Caveolin abundance is a marked decline in basal NO release, suggesting that the equilibrium between eNOS bound to Caveolin and Caveolinfree eNOS determines the basal component of eNOS-dependent NO release in endothelial cells. This interaction may be required to protect the cell from undesired, potentially cytoxic, or nonphysiological bursts of NO in response to small fluctuation in intracellular calcium (26,27).…”
mentioning
confidence: 99%
“…Having demonstrated that augmenting KLF2 levels within the Treg compartment is sufficient to promote peripheral tolerance, we next tested if this event could be replicated by simvastatin. Of note, statins have an immunosuppressive effect on endothelial cells, including decreased MHC class II expression, decreased expression of P-selectin and CD40, increased surface expression of complement inhibitory molecules, and increased production of nitric oxide (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Because the endothelial compartment contributes to symptoms of aGVHD (42)(43)(44)(45), these pleiotropic effects precluded the systemic use of simvastatin to test Treg-mediated tolerance.…”
Section: Increased Klf2 Expression Within the Treg Compartment Augmentsmentioning
confidence: 99%
“…Statins have been shown to improve NO synthesis by mechanisms unrelated to changes in serum LDL levels, including upregulation of eNOS expression 73 and reduced superoxide formation. 74,75 Additionally, statins stimulate endothelial NO production through a dramatic reduction in plasma membrane caveolin levels 76 (Figure 1). By interfering with cholesterol biosynthesis and lowering plasma membrane cholesterol levels, atorvastatin was shown to attenuate the expression of caveolin-1 ( Figure 5).…”
Section: Effects Of Hmg-coa Reductase Inhibitors On Cholesterol Micromentioning
confidence: 99%